Fishes of the Choctawhatchee River System in Southeastern Alabama and Northcentral Florida - Thomas P. Simon; Charles C. Morris; Bernard R Kuhajda; Carter R. Gilbert; Henry L. Bart Jr.; Nelson Rios; Paul M Stewart; Thomas P. Simon IV; Mitt Denney (Southeastern Fishes Council Proceedings, 2015)
The diversity and distribution of fish species occurring in the Choctawhatchee River drainage in southeastern Alabama and northcentral Florida were surveyed to obtain historical baseline information. Three hundred seventy-four sites were evaluated for species diversity and distribution in the drainage, including compilation of unpublished records from southeastern natural history museums. The greatest diversity at any single site was 37 species. Sixty-eight sites were represented by 15 species or more, and 26 sites were represented by a single species. The most frequently encountered species includes Gambusia holbrooki, Percina nigrofasciata, Esox americanus, Notropis texanus, Lepomis macrochirus, Cyprinella n. sp. cf venusta, Notropis amplamala, and Aphredoderus sayanus. New records for Hybopsis n. sp. cf winchelli and Etheostoma parvipinne were found in the drainage, and range extensions were found for 14 other species. Our study increases the known number of fish species in the Choctawhatchee River drainage to 132 species and two hybrids, including 83 native freshwater, 10 introduced freshwater, 24 estuarine, and 17 marine species.
Keywords: Distribution; Conservation Status; Species List; Marine; Estuarine; Freshwater